Aligning individual and organizational performance: goal alignment in federal government agency performance appraisal programs - Ayers, Rebecca S. (2015)
Performance appraisal programs are touted as a management control tool for implementing organizational goals and driving organizational performance but how these programs do that has not been evaluated. This research examines the extent to which goal alignment in federal agency performance appraisal programs enhances organizational performance. Two aspects of goal alignment are explored: actual embedding of organizational goals in performance plans (plan alignment) and employees$1 (Bknowledge of how their work relates to the agency$1 (Bs goals and priorities (employee alignment). Results indicate employee alignment increases organizational performance whereas plan alignment does not. Strategic management proponents should take note of this outcome. Furthermore, the overall quality of a performance appraisal program moderates the alignment and organizational performance relationship. Under conditions of high- and low-performance appraisal program expectations, employee alignment can influence organizational performance, but not as expected.s
Keywords: Strategic management; Federal government